Structural and Biochemical Study of the Mono-ADP-Ribosyltransferase Domain of SdeA, a Ubiquitylating/Deubiquitylating Enzyme from Legionella pneumophila. Issue 17 (17th August 2018) - Kim, Leehyeon; Kwon, Do Hoon; Kim, Bong Heon; Kim, Jiyeon; Park, Mi Rae; Park, Zee-Yong; Song, Hyun Kyu
Abstract: Conventional ubiquitylation occurs through an ATP-dependent three-enzyme cascade (E1, E2, and E3) that mediates the covalent conjugation of the C-terminus of ubiquitin to a lysine on the substrate. SdeA, which belongs to the SidE effector family of Legionella pneumophila, can transfer ubiquitin to endoplasmic reticulum-associated Rab-family GTPases in a manner independent of E1 and E2 enzymes. The novel ubiquitin-modifying enzyme SdeA utilizes NAD + as a cofactor to attach ubiquitin to a serine residue of the substrate. Here, to elucidate the coupled enzymatic reaction of NAD + hydrolysis and ADP-ribosylation of ubiquitin in SdeA, we characterized the mono-ADP-ribosyltransferase domain of SdeA and show that it consists of two sub-domains termed mART-N and mART-C. The crystal structure of the mART-C domain of SdeA was also determined in free form and in complex with NAD + at high resolution. Furthermore, the spatial orientations of the N-terminal deubiquitylase, phosphodiesterase, mono-ADP-ribosyltransferase, and C-terminal coiled-coil domains within the 180-kDa full-length SdeA were determined. These results provide insight into the unusual ubiquitylation mechanism of SdeA and expand our knowledge on the structure–function of mono-ADP-ribosyltransferases. Graphical Abstract: Unlabelled Image Highlights: The mono-ADP-ribosyltransferase domain of SdeA consists of two sub-domains termed mART-N and mART-C. Both mART-N and mART-C domains are necessary for efficient transfer of the ADP-ribose moiety of NAD + to the substrate ubiquitin. The crystal structure of mART-C of SdeA was determined in free form and in complex with NAD + at high resolution. The overall shape and spatial orientation of the modular domains of SdeA were determined.